Understanding Differences in Mental Health History and Behavioral Choices in a Community Sample of Individuals with and without Body Modifications. Issue 8 (2nd August 2016) - Giles-Gorniak, Amy N.; Vandehey, Michael A.; Stiles, Beverly L.
ABSTRACT: This study investigated the differences in mental health history and social, health, alcohol and substance, and sexual behaviors of individuals with and without body modification in a community sample. Previous research primarily focused on negative behavioral and psychological correlates of body modification practices in college student, juvenile delinquent, inpatient, and incarcerated populations. This tendency does not take into account changes in the demographics and motivations of individuals who obtain body modifications in the last two decades. The Community Body Modification Checklist was developed based on previous studies; reliability and validity for the measure were established using Cronbach's alpha and factor analysis. The results indicated that individuals with body modifications were not more likely to engage in risky behaviors or report a history of mental health problems when compared to non-modified persons; however, they were more likely to engage in social and health behaviors. These findings may be best explained by the body modification community becoming diversified by the middle class whose meanings, motivations, and usage of tattoos and piercings are unique.